Beyond Price: Does Perceived Quality Dictate Consumer Purchase Timing? - - Vika Diyah Ardiyanti; Iwan Hermawan; Gita Hindrawati; Luqman Khakim; Febrina Indrasari (Admisi dan Bisnis, 2026)
The intensifying competition in Indonesia’s coffee industry necessitates a deep understanding of the factors influencing purchase decisions. This study examines the effects of Consumer Value, Consumer Trust, and Product Variety on Purchase Decision, with Perceived Quality serving as a moderating variable. An associative quantitative approach employing moderation analysis was conducted on 675 urban coffee consumers who drink coffee at least four times per week, using a 1–6 Likert scale questionnaire. Classical assumption tests indicated no multicollinearity (VIF < 10) or heteroscedasticity (Sig. > 0.05). Although the data were not normally distributed, regression analysis remained valid due to the large sample size. Multiple regression results revealed that Consumer Value (β = 0.337; p < 0.001), Consumer Trust (β = 0.164; p < 0.001), and Product Variety (β = 0.173; p < 0.001) have significant positive effects on Purchase Decision, with Consumer Value being the strongest predictor. The Moderated Regression Analysis (MRA) further indicated that Perceived Quality significantly strengthens the relationship between Consumer Trust and Purchase Decision (β = 0.125; p < 0.001), but does not moderate the effects of Consumer Value or Product Variety. These findings reinforce the commitment-trust theory and the means-end model, highlighting the synergistic role of perceived quality in enhancing the influence of trust on purchase decisions. Practically, coffee businesses should maintain a high perception of quality through quality assurance, certification, and product consistency to maximize the impact of trust, while simultaneously sustaining product value and variety to achieve competitive advantage.